Glioblastoma-on-a-chip construction and therapeutic applications - Xie, Zuorun; Chen, Maosong; Lian, Jiangfang; Wang, Hongcai; Ma, Jingyun (Frontiers in Oncology, 2023)
Glioblastoma (GBM) is the most malignant primary intracranial tumor with a median overall survival of only 14 months, a very poor prognosis and a recurrence rate of 90%. Traditional in vitro models are difficult to reflect the complex structure and function of the GBM microenvironment in vivo. GBM-on-a-chip platforms could integrate biological or chemical functional units of tumor into a chip, mimicking in vivo functions of GBM cells. This technology has shown great potential for application in personalized precision medicine and promoting GBM immunotherapy. Over the last years, there have been efforts to construct GBM-on-a-chip models based on microfluidics and bioprinting. A number of research teams have begun to use GBM-on-a-chip models for the investigation of GBM progression mechanisms, testing of drug candidates, and therapeutic approaches in GBM. This review first briefly discusses the use of microfluidics and bioprinting technologies for glioblastoma-on-a-chip construction. Second, we classify non-surgical treatments for glioblastoma in pre-clinical research into three sections (chemotherapy, immunotherapy and other therapies) and pay attention to the investigation of the three sections based on glioblastoma-on-a-chip. Lastly, we point out organ-on-a-chip technology in therapeutic field is still at the initial stage, providing future perspectives for research directions in the field.